2018
DOI: 10.1177/1535370218777972
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Nav1.5 channels due to SCN5A mutations

Abstract: The voltage-gated sodium channel 1.5 (Nav1.5), encoded by the SCN5A gene, is responsible for the rising phase of the action potential of cardiomyocytes. The sodium current mediated by Nav1.5 consists of peak and late components (I and I). Mutant Nav1.5 causes alterations in the peak and late sodium current and is associated with an increasingly wide range of congenital arrhythmias. More than 400 mutations have been identified in the SCN5A gene. Although the mechanisms of SCN5A mutations leading to a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 134 publications
(100 reference statements)
1
36
0
Order By: Relevance
“…In addition, the Na þ /Ca 2þ exchanger (NCX) also plays a prominent role in modulating the APD in myocytes in failing hearts [58]. Late I Na is an integral part of the sodium current, which persists long after the fast-inactivating component and could contribute to the prolongation of the APD [59]. Late I Na is significantly increased in myocardial cells from failing human hearts and selected inhibition of late I Na is effective in shortening the QT interval and reducing ventricular arrhythmogenic activity [60].…”
Section: Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Na þ /Ca 2þ exchanger (NCX) also plays a prominent role in modulating the APD in myocytes in failing hearts [58]. Late I Na is an integral part of the sodium current, which persists long after the fast-inactivating component and could contribute to the prolongation of the APD [59]. Late I Na is significantly increased in myocardial cells from failing human hearts and selected inhibition of late I Na is effective in shortening the QT interval and reducing ventricular arrhythmogenic activity [60].…”
Section: Heart Failurementioning
confidence: 99%
“…Enhanced I Na-L can be observed in acquired conditions, such as hypertrophic cardiomyopathy, heart failure and drug-induced arrhythmias [112,113]. Mexiletine, a Vaughan-Williams class Ib antiarrhythmic agent, can shorten the APD by selectively suppressing I Na-L without affecting QRS duration [59]. We once reported that 12 patients with refractory TdP secondary to aLQTS were treated with oral mexiletine, 150-450 mg/day orally.…”
Section: Qt Prolongation With Tdpmentioning
confidence: 99%
“…Cardiac sodium current (I Na ) upstroke during depolarization phase is predominantly mediated by Na v 1.5 channel, which is the major voltage-gated sodium channel in the heart (Veerman et al, 2015). Mutations in Na v 1.5 are associated with a number of cardiac diseases such as long QT syndrome, AF and cardiomyopathy (Song and Shou, 2012;Shy et al, 2013;Han et al, 2018;Wilde and Amin, 2018). Matasic et al (2020) showed that NR increased I Na and reduced residual late I Na in vitro, and more importantly administration of NR decreased QTc in vivo.…”
Section: Arrhythmiamentioning
confidence: 99%
“…Additionally, GATA4 and GATA5 bind to the same binding region of the sodium voltage-gated channel alpha subunit 5 (SCN5A) gene promoter and co-activate the transcription of SCN5A gene (Tarradas et al, 2017). Mutations in the SCN5A gene cause a va-riety of arrhythmias, including Brudaga syndrome, long QT syndrome 3, sick sinus syndrome, cardiac conduction disease, progressive cardiac conduction defect and AF (Han et al, 2018). The SCN5A gene (chromosome 3p21) encodes the alpha subunit of the voltage-gated sodium channel 1.5 (Nav1.5) (Verkerk et al, 2018).…”
Section: Arrhythmiamentioning
confidence: 99%
“…GATA4, GATA5 and GATA6 maintain the expression of NKX2-5 by activating cx36.7 (Miyagi et al, 2016), the expression of NKX2-5 can directly up-regulate the expression of the Hes-related family basic helix-loop-helix (bHLH) transcription factor with YRPW motif 2 (HEY2), SCN5A and other genes (Anderson et al, 2018). SCN5A is closely related to arrhythmia (Han et al, 2018). Of note, HEY2 is a member of the bHLH transcription inhibitor family, the non-synonymous mutations of HEY2 are related to cardiac malfor-mations, such as congenital ventricular septal defect (Fardoun et al, 2019).…”
Section: Gata5/connexin 367(cx367)/nkx2-5/hey2 Signaling Pathwaymentioning
confidence: 99%